Criminalistic bases of formation of the methodology of investigation of theft committed by officers - Khlus, Alexander M. (Journal of the Belarusian State University. Law, 2020)
The author analyzed the modern private method of investigating theft by abuse of power, formed on the basis of their forensic characteristics. Its use in the investigation process does not provide practitioners with information about the presence and content of the elements of the material structure of specific thefts. This circumstance made it possible to conclude that the crimes are not completely forensic. According to the author, the forensic characteristics of embezzlement through abuse of authority should contain not only information about the general elements of their material structure, but also their description. Information about the elements of the material structure, as a result of a description of their characteristics, should be one of the main parts of the criminalistic characteristics of a crime. Knowledge of the elements of the material structure of the crime, combined with their forensic characteristics, provides a solid basis for developing a method for investigating thefts of this form.
Keywords: theft; forensic science; methodology; investigation; forensic characteristics; crime structure